The Impact of Improved Water, Sanitation, and Hygiene on Oral Rotavirus Vaccine Immunogenicity in Zimbabwean Infants: Substudy of a Cluster-randomized Trial. (29th March 2019) - Church, James A; Rukobo, Sandra; Govha, Margaret; Lee, Benjamin; Carmolli, Marya P; Chasekwa, Bernard; Ntozini, Robert; Mutasa, Kuda; McNeal, Monica M; Majo, Florence D; Tavengwa, Naume V; Moulton, Lawrence H; et al.
Abstract: Background: Oral vaccines have lower efficacy in developing compared to developed countries. Poor water, sanitation, and hygiene (WASH) may contribute to reduced oral vaccine immunogenicity. Methods: We conducted a cluster-randomized 2 × 2 factorial trial in rural Zimbabwe. Pregnant women and their infants were eligible if they lived in clusters randomized to (1) standard of care (52 clusters); (2) improved infant feeding (53 clusters); (3) WASH: ventilated improved pit latrine, 2 hand-washing stations, liquid soap, chlorine, infant play space, and hygiene counseling (53 clusters); or (4) feeding plus WASH (53 clusters). This substudy compared oral rotavirus vaccine (RVV) seroconversion (primary outcome), and seropositivity and geometric mean titer (GMT) (secondary outcomes), in WASH vs non-WASH infants by intention-to-treat analysis. Results: We included 801 infants with documented RVV receipt and postvaccine titer measurements (329 from 84 WASH clusters; 472 from 102 non-WASH clusters); 328 infants with prevaccination titers were included in the primary outcome. Thirty-three of 109 (30.3%) infants in the WASH group seroconverted following rotavirus vaccination, compared to 43 of 219 (19.6%) in the non-WASH group (absolute difference, 10.6% [95% confidence interval CI, .54%–20.7%]; P = .031). In the WASH vs non-WASH groups, 90 of 329 (27.4%) vs 107 of 472 (22.7%) were seropositive postvaccination (absolute difference, 4.7% [95% CI, –1.4% to 10.8%]; P = .130), and antirotavirus GMT was 18.4 (95% CI, 15.6–21.7) U/mL vs 14.9 (95% CI, 13.2–16.8) U/mL ( P = .072). Conclusions: Improvements in household WASH led to modest but significant increases in seroconversion to RVV in rural Zimbabwean infants. Clinical Trials Registration: NCT01824940. Abstract : Oral vaccines have lower efficacy in developing compared to developed countries. In a substudy of a cluster-randomized trial, improvements in household water, sanitation, and hygiene led to modest increases in seroconversion to oral rotavirus vaccine among rural Zimbabwean infants.